Low-power coding method in data transmission systems - Vladyslav, Yareshchenko; Kosenko, Viktor (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2024)
The object of the study is the Network-on-Chip (NoC) technology, which has become a popular choice for the on-chip communication architecture of modern System-on-Chip (SoC) devices. The subject matter of the article is methods of reducing dissipated power in NoC and SoC. The goal of the work is: development of a low-power coding method that allows for the efficient transmission or storage of information. The following tasks are solved in the article: analysis of classification methods for combinatorial structures, construction a system of typical representatives and analysis of their characteristics. The research methods are based on the use of set theory, system theory and combinatorics. The following results are obtained: analyzed factors that affect the dissipated power, considered principles of constructing energy-efficient codes. It is shown that switching activity significantly affects the total power and one of the effective methods for reducing switching activity during communication between devices or on-chip communication is the use of low-power coding methods. A method of hierarchical classification of unit distance codes and algorithms for solving step-by-step problems have been developed. The method is based on the invariant approach and construction of a system of different representatives. Estimates of their number have been obtained, characteristics have been determined, and catalogs of typical representatives have been formed. Conclusions. The article analyzes factors that affect dissipated power, and considers the principles of constructing energy-efficient codes. A method of hierarchical classification of single distance codes and algorithms for solving step-by-step problems have been developed, and catalogs of typical representatives have been formed. The application of the developed method will allow developers to analyze and select codes with the best properties and, as a result, obtain better results in terms of network delays, energy costs, and other design limitations for computer systems.